Insane Colony - Valdizán, Hermilio (1919)
The first cases of insanity among the conquerors of this land of Peru, giving news of the chroniclers of the Indies, is the saddest of Pedro de Alcon, one of the comrades of the conqueror Don Francisco Pizarro one of thirteen in the Gallo Island, showing their effort and loyalty, remained loyal to warlord thrown and refused to leave him.